Elections as Vehicles for Change? Explaining different outcomes of democratic performance and government alternation in Africa - Edalina Rodrigues Sanches; José Jaime Macuane (Cadernos de Estudos Africanos)
Does having more regular elections improve democratic performance in Africa? And have elections transformed the patterns of alternation in government? To answer these questions, two analyses are conducted drawing on an original dataset of 179 elections in 27 African countries, from the founding multiparty elections until 2019. The first tests the effects of alternation in government on democratic performance and shows that while alternation in government in the founding elections improves democratic performance, opposition victories in subsequent elections do not produce democratic gains. The second examines why alternation in government is more frequent in certain countries than in others; and reveals that the odds of turnover are increased by alternation in government in the founding elections, the level of political competition and the quality of elections. These findings contribute to literature linking elections, democracy and turnover in Africa.